Relationship between metabolic syndrome and osteoarthritis: The Fasa Osteoarthritis Study. (December 2017) - Askari, Alireza; Ehrampoush, Elham; Homayounfar, Reza; Arasteh, Peyman; Naghizadeh, Mohammad Mehdi; Yarahmadi, Mohammadreza; Tarbiat, Niloofar; Eghbali, Seyed Sajjad
Abstract: Background: An association between metabolic syndrome (MeS) and osteoarthritis (OA) has been reported in recent years; however, conflicting findings have been reported regarding this matter. Inhere we evaluated the relationship between different components of MeS and OA in a Fasa osteoarthritis registry (FOAS). Methods: The registry includes all OA cases who referred to Fasa hospital (Iran) since 2013. Overall, 131 patients with OA with a Kellgren & Lawrence (K&L) score >1 and 261 controls were compared. Results: Overall, 82.4% of individuals in the OA group and 40.8% of participants in the control group had MeS (P < 0.001). Patients with OA had a 6.8 (95% CI: 4.1–11.4) higher chance of acquiring MeS. After adjusting for sex, age, and BMI, odds' ratio (OR) for acquiring MeS in OA group increased to 10.9 (95% CI: 5.5–21.8). Among MeS criteria's, high waist circumference (WC) has strongest correlation for acquiring OA (OR = 27.535, 95% CI: 6.003–126.306). Conclusion: Our findings revealed that metabolic markers are strongly associated with OA and the addition of each component of the MeS, significantly increases the risk of developing OA, therefore control of metabolic factors and appropriate screening must be considered in health policy making and prevention programs.